PENGGUNAAN SITUS JEJARING SOSIAL YOUTUBE DALAM PEMBELAJARAN FIQIH DI MTS MUHAMMADIYAH SALAM MAGELANG - Nofa Kharida; Zainuddin, Mohammad Riza (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2024)
The use of the YouTube social networking site in Islamic religious education learning in this era is very necessary to answer the challenges of the era where students will more easily receive understanding through audio and visual video. This research explores the integration of the YouTube social networking platform into learning fiqh subjects at MTs Muhammadiyah Salam Magelang. Using qualitative methods such as observation, interviews, and document analysis, this research investigates implementation strategies for student acceptance, impacts, and challenges for teachers related to incorporating the use of YouTube into Fiqh learning. These findings explain the use of YouTube as an educational tool in facilitating student engagement and understanding in Islamic religious studies. This study contributes to understanding the dynamic relationship between technology and Islamic religious education, providing valuable insights for educators in optimizing pedagogical approaches in teaching Islamic education. This research underscores the importance of utilizing digital platforms such as YouTube to enhance learning experiences and encourage meaningful engagement in religious education in Islamic school.